1994
DOI: 10.1159/000163881
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Cytokine Modulation of Intercellular Adhesion Molecule-1 Expression on Systemic Sclerosis Dermal Fibroblasts

Abstract: Our objective was to study the regulation of intercellular adhesion molecule-1 (ICAM-1) expression by cytokines on cultured fibroblasts obtained from systemic sclerosis and normal skin. ICAM-1 expression on dermal fibroblasts obtained from diffuse systemic sclerosis patients with early disease (≤ 2 years) and normal dermal fibroblasts incubated with and without cytokines was measured by radioimmunoassay and flow cytometry. Systemic sclerosis dermal fibroblasts expressed lower basal levels of ICAM-1 than did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
4
10
0
Order By: Relevance
“…Koch et al reported that TNFα expression was increased on SSc stratum granulosum, especially in early SSc and suggested that TNFα may play a part in the early inflammatory stage of SSc 16. Systemic sclerosis dermal fibroblasts were reported to be hyperresponsive to TNFα and expression of ICAM-1 was increased to a greater degree in response to TNFα stimulation 17. Based on these and other reports9 10 we suggest that TNFα might play a part in the pathogenesis of scleroderma.…”
Section: Discussionsupporting
confidence: 50%
“…Koch et al reported that TNFα expression was increased on SSc stratum granulosum, especially in early SSc and suggested that TNFα may play a part in the early inflammatory stage of SSc 16. Systemic sclerosis dermal fibroblasts were reported to be hyperresponsive to TNFα and expression of ICAM-1 was increased to a greater degree in response to TNFα stimulation 17. Based on these and other reports9 10 we suggest that TNFα might play a part in the pathogenesis of scleroderma.…”
Section: Discussionsupporting
confidence: 50%
“…Systemic sclerosis dermal fibroblasts were reported to be hyperresponsive to TNF-a, and expression of intercellular adhesion molecule 1 (ICAM-1) was increased to a greater degree in response to TNF-a stimulation (Cho et al 1994). Based on these and other reports (Moffatt and Cookson 1997;Fernandez-Arquero et al 1999), we suggest that TNF-a might play a role in the pathogenesis of scleroderma.…”
Section: Introductionmentioning
confidence: 55%
“…Studies conducted by Thornton et al have found lower concentrations of TNF-α to stimulate fibroblast synthesis and higher levels to be inhibitory [15]. SSc analyses conducted in vitro have implicated TNF-α as a potential contributor to fibrosis, demonstrating SSc dermal fibroblasts to be hyperresponsive to TNF-α [16]. In vivo studies have illustrated elevated serum levels of TNF-α to be significantly correlated with the presence of pulmonary fibrosis [17].…”
Section: Th1 Associated Cytokinesmentioning
confidence: 99%